Profil Laboratorium Ipa Di MTs Negeri Surakarta II Dalam Menunjang Pelaksanaan Kurikulum 2013 Tahun 2014/ 2015 - Wulandari, Marsida (2015)
A laboratory is one of useful learning source that used to give students a real experience, being supporting factor of 2013 curriculum. The success of 2013 curriculum should be supported by equipment ability and lab work material because 2013 curriculum actually uses a scientific learning which demands students about desire find out (discovery learning). This study aims to identify the comprehensiveness of equipments and supporting facilities in science laboratory of MTSN II Surakarta to equip 2013 curriculum implementation. The type of research is descriptive qualitative method, the techniques are laboratory observation, material inventory documentation, laboratory design, also equipments and facilities in science laboratory, interviewing VII grade of science teachers. The research findings conclude that the comprehensiveness of profile science laboratory of MTSN II Surakarta, included good category (74,3%) with laboratory design percentage 70% (good), completeness of lab work equipments 73,17% (good), completeness of public facilities 87, 5% (very good), and completeness of special facilities 66,7% (good).